The Design and Implementation of Massive Open Online Course (MOOC) for Ordinary Differential Equations (ODE) - Md Said, Junaida; Arul, Elizabeth; Abdul Razak, Samsiah; Azila Yahya, Nur; Husna Jamian, Nural (International Journal of Engineering and Technology, 2018)
Ordinary Differential Equations (ODE) is taken by students in the mathematics, science or engineering programs in Universiti Teknologi MARA (UiTM). This course was originally taught in the traditional way with the lecturer as the instructor. In 2014, this course evolved into the blended-learning mode i.e. a combination of classroom sessions and online sessions using the university learning management system. In 2017, a team of lecturers in the Tapah campus of UiTM decided to develop an instructional design of ODE using the MOOC platform. Students would then use the MOOC during the blended-learning hour. Five modules are offered in this MOOC. Lecture notes are presented using Prezi together with instructional videos and self-checking exercises. 55 students enrolled for the MOOC and were surveyed to gauge the initial impact of the MOOC as an instructional tool. More than 50% of the students said that the MOOC absolutely helped them to better understand the classroom sessions. Most of the students put in maximum effort in accessing the MOOC. The MOOC also helped to build up self-confidence of students in the course material. It is hoped that as the MOOC is further refined and improved, more students will benefit from the MOOC.Â Â